Flume-based Experimental Study on Wave Prevention and Sand Fixation Functions of Sand Barriers Applied to Coral Sandy Coastlines - Qu Jianju; Li Shaowu; Jiang Chong; Hu Wenli; Liu Ye; Li Qihang (Shuitu baochi tongbao)
[Objective] The flume simulation research on wave prevention and sand stabilization counter measures for coral sandy coastlines were studied in order to provide a theoretical basis for the project to protect coastlines against wave erosion along the Dengloujiao shoreline, located in the Xuwen National Coral Reef Nature Reserve on the Leizhou Peninsula, and to provide technical support for similar coastal areas. [Methods] The coastal erosion protection effect of san-dbag barrier measures was determined for the Dengloujiao coastline using a flume experiment simulation method. [Results] ① The composite effect of the overall structure of the diamond-shaped sand-bag barrier had a significant impact on the stability of the sand barrier. Two groups of sand barriers with a diameter of 5 cm or above was able to achieve self-stability. Calculated according to the gravity similarity criterion, this was equivalent to 50 cm diameter of the prototype; ② The sand-bag barrier achieved sediment fixation by increasing the roughness of the bed surface, weakening the hydrodynamic strength, and thereby reducing the intensity of sediment transport. As the diameter of the sand barrier increased, its shielding effect became more significant; ③ For a wave period of 1.90 s and a water depth of 0.4 m, the height of sand ridges observed in the experiment were 3—4 cm. Therefore, in practical projects, sand barriers with a diameter of 50 cm or more can prevent and control the migration of sand waves and sand ridges; ④ The sand barrier arranged in a diamond shape was less affected by oblique waves and had better stability than the sand barrier arranged in a normal direction. Therefore, it is advisable to use a diamond-shaped sand barrier to reduce the effect of oblique waves. [Conclusion] The use of sand-bag barriers as protective materials for coastal erosion not only achieved the goal of sand control, but also produced favourable ecological and environmental protection effects. These results could provide important scientific guidance and have significant and practical promotion value.